Wybrane aspekty jakości życia w Uniejowie w opinii mieszkańców - Mularska-Kucharek, Monika (Biuletyn Uniejowski, 2014)
High quality of life is increasingly regarded as the main development goal at local, regional, national and international level. Representatives of territorial units employ various strategies designed to improve the residents’ living conditions, which translates into higher quality of life. This, however, would not be possible without taking into account the opinions and preferences of the residents. Public opinion is a key element in taking actions to enhance the quality of life because it makes the management of this process more effective. This article presents the results of surveys concerning evaluation of selected aspects of the quality of life in Uniejów, such as accessibility of certain services and functioning of key institutions in the town. The findings have not only the cognitive character but can also be valuable in practical applications.